IMPACT OF INFORMATION COMMUNICATION TECHNOLOGY ON POVERTY ALLEVIATION IN NIGERIA: A STUDY OF NATIONAL POPULATION COMMISSION, ABUJA (AUN INTERNATIONAL CONFERENCE, 2025)
This study investigates the transformative role of Information and Communication Technology (ICT) in addressing poverty-driven food crises in Nigeria, using the National Population Commission (NPC), Abuja, as a focal institution. Situated within the broader context of national food insecurity and socio-economic vulnerability, the research adopts a multidisciplinary approach combining insights from public administration, digital innovation, rural development, and food systems. The study evaluates the impact of four major ICT tools—Automated Data Collection Systems (ADCS), Social Media Platforms (SMP), Internet & Mobile Technologies (IMT), and E-Learning Platforms (ELP)—on NPC’s poverty alleviation strategies that indirectly shape food access and resource distribution. Findings indicate that ICT deployment significantly improves intervention outcomes, with ADCS enhancing real-time data accuracy and enabling better-targeted food security programs (β = 0.762). SMP strengthens community mobilization and feedback loops (β = 0.748), IMT bridges the digital divide in remote areas, and ELP equips individuals—especially youth and women—with skills relevant to agricultural productivity and post-harvest value chains. Regionally, disparities in ICT access between rural and urban communities (SD range = 0.559–0.907) reveal the urgent need for context-sensitive implementation frameworks in the South-East and North-East zones where food insecurity is most acute.The research contributes to policy by validating a scalable ICT impact model adaptable for national food security planning. Key recommendations include: expanding digital infrastructure and mobile coverage in farming communities; integrating e-learning modules into agricultural extension services; leveraging ADCS for targeted food distribution and emergency nutrition interventions; and fostering inter-agency collaboration between the NPC, Ministry of Agriculture, and NITDA to drive technology-enabled solutions to hunger and malnutrition.